2020
DOI: 10.1590/s2175-97902019000318599
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of ibuprofen with itraconazole and fluconazole against Cryptococcus neoformans

Abstract: The present study investigated the association of the non-steroidal anti-inflammatory drug ibuprofen with itraconazole, fluconazole and amphotericin B against Cryptococcus neoformans isolates. The minimal inhibitory concentration (MIC) was found according to M27-A3 protocol and in vitro interactions were evaluated using checkerboard microdilution method. Synergism was demonstrated between azoles and ibuprofen for most isolates. However, no synergistic effects were seen when amphotericin B was combined with ibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…While there is evidence to suggest a degree of synergism between ibuprofen and itraconazole when used to treat fungal infections, it has also been recognised that itraconazole's binding of SMO protein is independent of its ability to inhibit CYP450-dependent ergosterol synthesis in fungi cell membranes. 5,10 Although innumerable review articles discuss the anti-Hh properties of intraconazole in molecular and murine studies, this systematic review highlights that the evidence on the clinical efficacy of intraconazole in the treatment of BCC remains sparse. Its use in locally advanced and/or metastatic BCC, where its application is most likely to be relevant, is limited to case reports/series as monotherapy, with the addition of small phase 2 proof of concept studies for when used in combination with other Hh pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is evidence to suggest a degree of synergism between ibuprofen and itraconazole when used to treat fungal infections, it has also been recognised that itraconazole's binding of SMO protein is independent of its ability to inhibit CYP450-dependent ergosterol synthesis in fungi cell membranes. 5,10 Although innumerable review articles discuss the anti-Hh properties of intraconazole in molecular and murine studies, this systematic review highlights that the evidence on the clinical efficacy of intraconazole in the treatment of BCC remains sparse. Its use in locally advanced and/or metastatic BCC, where its application is most likely to be relevant, is limited to case reports/series as monotherapy, with the addition of small phase 2 proof of concept studies for when used in combination with other Hh pathway inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike itraconazole, COX‐2 inhibitors have not been shown to exhibit anti‐Hh pathway properties. While there is evidence to suggest a degree of synergism between ibuprofen and itraconazole when used to treat fungal infections, it has also been recognised that itraconazole’s binding of SMO protein is independent of its ability to inhibit CYP450‐dependent ergosterol synthesis in fungi cell membranes 5,10 …”
Section: Discussionmentioning
confidence: 99%
“… 41 It was shown that ibuprofen can alter the expression of the genes encoding the efflux pumps and that it may also act directly as an efflux pump blocker. 42 , 43 …”
Section: Introductionmentioning
confidence: 99%
“…albicans. , A similar effect was observed for a combination of FLC and FK506, a 23-membered-ring macrolide immunosuppressant, that also acts as a broad-spectrum inhibitor of pleiotropic drug resistance ATP-binding cassette transporters. ,, FLC -resistant isolates revert to FLC susceptible after incubation with ibuprofen yet retain high levels of expression of CDR1 and CDR2 efflux pumps . It was shown that ibuprofen can alter the expression of the genes encoding the efflux pumps and that it may also act directly as an efflux pump blocker. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation